Pengaruh Iklim Kerja, Motivasi dan Kepuasan Kerja Terhadap Kinerja Guru SMA Negeri Tapanuli Selatan - Ria Juliani Rambe (UMSU, 2023)
This study aims to determine the effect of work climate, teacher motivation and job satisfaction on teacher performance. This research is a quantitative research with a correlational approach. This study took place at SMA Negeri Tapanuli Selatan. The sample in this study found 183 teach The results of this study are jointly significant, that is, the results of the Fcount test are 148.415, Ftable is 2.710, which is greater than the table. Because Fcount Ftable or 148.415 2.710 then Ha is accepted and Ho is rejected. It can be explained that the R square value is 0.837. This means that the variables of work climate, teacher motivation and job satisfaction affect teacher performance together by 83.7%, and the remaining 16.3% is determined by other reasons not examined. So it can be concluded that there is an influence of work climate, teacher motivation and job satisfaction affect teacher performance.